PEMBINAAN KREATIVITAS RELIEF WASSEBAGAI MEDIA PEMBELAJARAN - Suwarna, Trie Hartiti Retnowati (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2012)
The purpose of this public service is to produce "was" relief as alearning media in the Kindergarten and the simulation of the way to used itin the Kindergarten B grade. The target is all of the Kindergarten teachers inTempel, Sleman, and DIY district. The other purpose is to increase the artapresiation of the Kindergarten teachers concerning of the "was" relief as alearning media. The activities was due to on 26, 27, 28 July, 2011 inNgestirini Kindergarten, Kadisono, Tempel, Sleman, DIY.The method of this public service is to applied human approach,speech, discuss and assessment method.The results of this service are: (1) The realization of "was' relief has33 amount, sized 60 cm x 40 cm, this sized has been qualified as thelearning media in the Kindergarten, which aestetic, educative, and theauthority technique, (2) The simulation to four teacher in NgestiriniKindergarten for B2 and B3 grade have been done.